THEORETICAL AND METHODOLOGICAL APPROACHES TO THE STUDY OF VIRTUALIZATION IN A DIGITALIZED SOCIETY (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the process of virtualization that arises from the activity of individuals in cyberspace within the context of a digitalized society, treating it as a socio-philosophical phenomenon. The study demonstrates that virtualization, as a new and non-real form of socialization, has become a pressing research issue at the intersection of philosophy, psychology, sociology, and religious studies. Drawing on theoretical frameworks developed by key Western and Russian scholars including Sorokin, Durkheim, Baudrillard, Krueger, Sutherland, Lanier, Ivanov, Maslow, and others the article traces the evolution of the concepts of “virtual reality” and “virtualization,” and analyzes the principal methodological approaches applicable to the study of virtualization in the information society. The article concludes that virtualization constitutes a transformation of real social relations into a technological field and proposes a set of complementary methodological tools for its further investigation.
Keywords: virtualization; virtual reality; cyberspace; digitalized society; socialization; information society; social identity; virtual space; cyberspace; identification process.